2017
DOI: 10.24017/science.2017.2.11
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Color Vision Deficiency among Students in Hajand and Amad High Schools in Shekhan City

Abstract: Abstract:Color vision deficiency is a condition affecting human's ability to see or recognize specific colors. It is mostly genetic, X-linked recessive inheritance and thus, is more common among males than females. This cross sectional study was done to find the prevalence of color vision deficiency among high school students in Shekhan city and to find the relation of color vision deficiency with different races. The study has been conducted in two high schools that were present inside Shekhan city at the tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
2
3
2
Order By: Relevance
“…The overall prevalence of CCVD in the present study was lower compared to the previous studies such as in Addis Ababa (Ethiopia), 4.52%, by Abebe and Wondimkun [24], in Saudi Arabia, 3.36%, by Oriowo and Alotaibi [12], in Manipur (India), 5.28 %, by Shah et al [13], in Shekhan City/Kurdistan region (Iraq), 3.28%, by Abdulrahman [14], in Welkite town (central Ethiopia), 4.10%, by Woldeamanuel and Geta [15] but higher than a report in Bhopal (India), 2.50% by Gupta et al [16]. The lower prevalence of CCVD in the present study relative to other studies conducted in Ethiopia [24,25], could be due to the larger sample size of the current study.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…The overall prevalence of CCVD in the present study was lower compared to the previous studies such as in Addis Ababa (Ethiopia), 4.52%, by Abebe and Wondimkun [24], in Saudi Arabia, 3.36%, by Oriowo and Alotaibi [12], in Manipur (India), 5.28 %, by Shah et al [13], in Shekhan City/Kurdistan region (Iraq), 3.28%, by Abdulrahman [14], in Welkite town (central Ethiopia), 4.10%, by Woldeamanuel and Geta [15] but higher than a report in Bhopal (India), 2.50% by Gupta et al [16]. The lower prevalence of CCVD in the present study relative to other studies conducted in Ethiopia [24,25], could be due to the larger sample size of the current study.…”
Section: Discussioncontrasting
confidence: 80%
“…The prevalence of colour congenital blindness varies from race to race and differs in different geographic areas. For example, the prevalence is 3.36% in Saudi Arabia [ 12 ], 5.28 %, in Manipur (India) [ 13 ], 3.28% in Shekhan City/Kurdistan region (Iraq) [ 14 ], 4.10% in Welkite town (central Ethiopia) [ 15 ] and 2.50% in Bhopal (India) [ 16 ]. For the gene being X-linked, the frequency of CCVDs varies between males and females and it is usually more frequent in males.…”
Section: Introductionmentioning
confidence: 99%
“…The overall incidence of CCVD in this study is comparable to the prevalence rates of 2.2 % in Durban, South Africa [8], and slightly higher than 1.5% the report among school children in Zaria, Northern Nigeria [9]. However, it is lower compared to incidence rates 5.28 % in Manipur, India [10], 3.28% in Shekhan City/Kurdistan region, Iraq [11] and 2.85% among university students [2]. The difference in the incidence of CCVD from the current study could be due to difference in study populations, cultural/religious, geographical, ethnicity and techniques of color vision test [2,5,6,10,12].…”
Section: Discussionsupporting
confidence: 67%
“…The overall prevalence of color vision deficiency is 5.63% in this study, furthermore the prevalence among boys is 9.6% and among girls is 1.64%, which is above the hispanic range. Other studies that had been conducted in Kurdistan region and Iraq revealed that the prevalence of color vision deficiency in Shekhan high schools students (sample size n = 640 students, 283 males and 357 females) was 6.8% of male and 0.8% of female pupils 16 , which is lower than the prevalence of this study for both males and females, which may be due to the multi-ethnic society of Shekhan district whish is component of Muslims, Yazidis, and Christians, as among 640 students enrolled in Shekhan study, 97 were Yazidis and 3 were Christians, estimating 16% of the sample size, while in the current study, 3 students were Yazidis, and 3 were Christians, estimating 0.6% of the total sample size. Another study conducted among different ethnic groups of students in Erbil city 17 (n =1856, 1275 males and 581 females), the prevalence of color vision deficiency was 8.47% of males and 1.37% of females students, which is lower than the results of this study taking in consideration the larger sample size of the mentioned study, which is as twice as the sample size in our study.…”
Section: Discussionmentioning
confidence: 93%